NON-GOLD FIDUCIARY SECURITY VALUE CALCULATION SYSTEM BASED ON THE RAHN CONTRACT: A STUDY ON PT. PEGADAIAN SYARI'AH UNIT DARUSSALAM - Riska Yulianti; Muhammad Syuib (JURISTA: Jurnal Hukum dan Keadilan, 2019)
The amount of financing that will be provided by the pawnshop is determined by the value of the collateral submitted by the customer to the management of PT Pegadaian Syari'ah. The debtor customer must meet the standardisation of the collateral object that applies to PT Pegadaian Syari'ah and must identify the value of the collateral object through the process of estimating the price of the collateral object submitted by the debtor customer. So the focus of the problem as the object of study in this research on the guarantee system, especially regarding the guarantee valuation system provided by debtor customers in the form of goods other than gold, usually in the form of vehicles, both cars and motorbikes. The research questions in this thesis are how is the assessment of the feasibility of non-gold fiduciary security objects accepted as collateral at PT Pegadaian Syari'ah Darussalam Unit? how is the standardisation of the price of non-gold fiduciary collateral value set by PT Pegadaian Syari'ah Darussalam Unit? and how does the value of non-gold fiduciary security objects affect the financing provided by PT Pegadaian Syari'ah Darussalam Unit?. In this thesis research, the author uses qualitative research type, this research uses descriptive analysis method based on library research and field research data. The results of the research found that in calculating the value of non-gold fiduciary collateral at PT Pegadaian Syari'ah Darussalam Unit is guided by the local market price provisions issued regularly by the head office. While the assessment of the feasibility of the non-gold fiduciary guarantee object received as collateral at PT Pegadaian Syari'ah Darussalam Unit is determined by directly seeing the feasibility of the guarantee object by PT Pegadaian Syariah to the customer, and also evaluating the real conditions of the feasibility assessment of the object as collateral for Arrum financing. The estimated value of the goods is determined based on the percentage of the price of the goods, which is guided by the Local Market Price and which is sourced in several places such as agents and online sites. Things that affect the value of the collateral object, namely the object and business, both of which must be balanced, the year of expiration of the motorbike and the physical condition of an object. In the concept of fiqh muamalah, there are no specific provisions regarding the calculation of the value of collateral in this rahn contract. And in some pawn hadiths, clear information is also not obtained, so that the parties can flexibly make their own guarantee value.